Three-dimensional flow dynamics and mixing in a gas-centered liquid-swirl coaxial injector at supercritical pressure - Wang, Xingjian; Wang, Yanxing; Yang, Vigor (Physics of fluids (1994), 2019)
Three-dimensional flow dynamics and mixing in a gas-centered liquid-swirl coaxial injector at supercritical pressure is numerically studied using the large-eddy-simulation technique. In this class of injectors, typical of liquid-fueled propulsion engines, high-temperature gaseous oxygen (GOX) is axially delivered into the center tube and kerosene is tangentially injected through discrete orifices into the coaxial annulus. The operating conditions and geometry mimic those of the main injector elements used in staged-combustion propulsion engines. The present work details the full three-dimensional flow evolution over the entire injector configuration, including axial and circumferential dynamics that are essential for small-scale mixing between GOX and kerosene. Various key flow structures and instability mechanisms in the injector, including axial and azimuthal shear-layer instabilities, secondary instabilities (baroclinic torque and volume dilatation), centrifugal instability, flow recirculation, and acoustic motion, are identified. The significance of these instability mechanisms is explored in the context of streamwise and azimuthal vorticity transport. The GOX core is found to exhibit a hexagonal shape, mainly due to the interactions of vortex rings detached from the center post and coaxial annulus. For comparison, a cylindrical sector of the configuration is also simulated. The results of the present study will support the design and development of high-performance injectors for future propulsion applications.